INNOVATIVE MODEL OF TRAINING OFFICERS IN CIVIL UNIVERSITY - Alexander N. Abramov; Leonid Yu. Rotkov; Alexey V. Simonov; Valeriy V. Trembovetskiy (Высшее образование в России)
The article demonstrates the necessity of expanding the capabilities of the system of higher military institutes and military training centers of civilian universities to ensure the increasing requirements of the Russian Ministry of Defence for training of officers. The article considers the model of the special officers' training for military service under the contract by the innovative educational trajectory on the basis of a civil university, having in his structure the military department (department of military training). The model has been developed at Lobachevsky State University ofNizhni Novgorod (UNN). It enables to prepare an officer for two different fields of study in higher education. The innovative model is presented for officer training area "Foreign regional studies" (Bachelor's programme) followed by training by the programme of "Psychology" (Master). The implementation of innovative model does not require changes to existing legal acts.